Legal Redesignation of Central and Regional Authorities to Strengthen Sinergity in Public Services - Malicia Evendia; Ade Arif Firmansyah (Universitas Syiah Kuala, 2021)
This study aims to analyze and find the ideal legal design of the relationship of authority between the central and regional governments in order to strengthen synergy in public services. In essence, the granting of autonomy to the regions is directed at accelerating the realization of public welfare, through the implementation of government affairs. Concurrent government affairs as stipulated in Law no. 23/2014, is a governmental affair that is divided between the central government, provincial government and district/city governments. In practice, when problems occur in the implementation of concurrent affairs which fall under the central authority, the regional government is in a powerless position. This research uses normative legal research methods with statutory, case, and conceptual approaches. The results of this study indicate that: the absence of a legal instrument that accommodates and bridges central and regional authorities causes problems that occur in the community to continue and do not immediately find solutions. It is necessary to have legal instruments in the form of government regula-tions in bridging the authority of the central and regional governments to build synergy in public services, especially to resolve conflicts that occur in society so that government administration can run effectively.